Analisis Implementasi Load Balancing dengan Metode Source Hash Scheduling pada Procol SSL - Raden Arief Setyawan (Jurnal EECCIS, 2014)
The Course programming period give the highest load for academic server (SIAM) of UB. More than 65000 student will access the system concurrently. There for, the load balancing mechanism is required to improve system capacity and prevent the access failure SIAM using SSL mechanism to provide protection for academik data transaction. SSL do the handshaking process to maintain the connectivity of the web browser. In addition, the client and the server will establish a session recording mechanism to keep the identity of a connection to prevent repeat login. This study tried to implement a source-hash scheduling mechanism on the load balancing system. This mechanism subjected to prevent the termination of a session connection which has been formed. The results shows that the source hash scheduling has increased the capacity of the system to handle as many as 9.02594 million requests from 65 087 different IP within 1 day. And provide total data throughput of 169 537 010 395 Bytes (169 GB) in a single day getIndex Terms—Load Balancing, Source Hash Scheduling